Production of myo‐inositol: Recent advance and prospective. (21st May 2021) - Li, Yunjie; Han, Pingping; Wang, Juan; Shi, Ting; You, Chun
Abstract: Myo ‐inositol and its derivatives have been extensively used in the pharmaceutics, cosmetics, and food and feed industries. In recent years, compared with traditional chemical acid hydrolysis, biological methods have been taken as viable and cost‐effective ways to myo ‐inositol production from cheap raw materials. In this review, we provide a thorough overview of the development, progress, current status, and future direction of myo ‐inositol production (e.g., chemical acid hydrolysis, microbial fermentation, and in vitro enzymatic biocatalysis). The chemical acid hydrolysis of phytate suffers from serious phosphorous pollution and intricate product separation, resulting in myo ‐inositol production at a high cost. For microbial fermentation, creative strategies have been provided for the efficient myo ‐inositol biosynthesis by synergetic utilization of glucose and glycerol in Escherichia coli . in vitro cascade enzymatic biocatalysis is a multienzymatic transformation of various substrates to myo ‐inositol. Here, the different in vitro pathways design, the source of selected enzymes, and the catalytic condition optimization have been summarized and analyzed. Also, we discuss some important existing challenges and suggest several viewpoints. The development of in vitro enzymatic biosystems featuring low cost, high volumetric productivity, flexible compatibility, and great robustness could be one of the promising strategies for future myo‐ inositol industrial biomanufacturing.